Evidence for Centromere Drive in the Holocentric Chromosomes of Caenorhabditis - Zedek, František (Public Library of Science, 2012)

(untitled)
In monocentric organisms with asymmetric meiosis, the kinetochore proteins, such as CENH3 and CENP-C, evolve adaptively to counterbalance the deleterious effects of centromere drive, which is caused by the expansion of centromeric satellite repeats. The selection regimes that act on CENH3 and CENP-C genes have not been analyzed in organisms with holocentric chromosomes, although holocentrism is speculated to have evolved to suppress centromere drive. We tested both CENH3 and CENP-C for positive selection in several species of the holocentric genus Caenorhabditis using the maximum likelihood approach and sliding-window analysis. Although CENP-C did not show any signs of positive selection, positive selection has been detected in the case of CENH3. These results support the hypothesis that centromere drive occurs in Nematoda, at least in the telokinetic meiosis of Caenorhabditis.